The effects of storage temperature on the quality and phenolic metabolism of whole and minimally processed kale leaves - Adriano do Nascimento Simões; Silvino Intra Moreira; Paulo Roberto Mosquim; Nilda de Fátima Ferreira Soares; Rolf Puschmann (Acta Scientiarum. Agronomy, 2014)
We studied the effects of storage temperature on the activities of phenylalanine ammonia-lyase (PAL), peroxidase (POD) and polyphenol oxidase (PPO) in minimally processed kale (Brassica oleracea var. acephala) that was stored for 15 and 9 days at 5 ± 1ºC and 10 ± 1ºC, respectively. The main visual evidence for quality loss in whole leaves was yellowing and loss of turgescence. Minimally processed leaves presented significant browning, indicating increased POD and PPO activities. The PAL activity in minimally processed leaves stored at 5ºC was fourfold higher than that of whole leaves after two days of storage. We showed that minimal processing influenced PAL, POD and PPO activities. The activity of all enzymes studied increased during storage, indicating that changes in phenolic metabolism play an important role in the decline of kale quality. PAL activity increased rapidly at the beginning of storage and exhibited a reduced rate of increase over time, while the PPO and POD activities increased continuously over time. The storage at 5 ° C was a great ally in delaying changes in phenolic metabolism; however, the absolute PAL activity was higher at 5 than at 10ºC.